2011
DOI: 10.1021/ol2010424
|View full text |Cite
|
Sign up to set email alerts
|

The Davis–Beirut Reaction: N1,N2-Disubstituted-1H-Indazolones via 1,6-Electrophilic Addition to 3-Alkoxy-2H-Indazoles

Abstract: A variety of electrophiles (anhydrides, acid chlorides, carbonochloridates, sulfonyl chlorides, and alkyl bromides) react with 3-methoxy-2H-indazole (1a), benzoxazin[3,2-b]indazole (1d), and oxazolino[3,2-b]indazole (1e) – substrates available by the Davis-Beirut reaction – to yield a diverse set of N1,N2-disubstituted-1H-indazolones. With certain electrophiles, an AERORC (Addition of the Electrophile, Ring Opening, and Ring Closure) process on indazole 1d results in indazoloindazolone formation. An intriguing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Azides 8 and 9 were prepared from their corresponding bromoketone and bromoalkane, respectively (Figure 2). 37,38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Azides 8 and 9 were prepared from their corresponding bromoketone and bromoalkane, respectively (Figure 2). 37,38 …”
Section: Resultsmentioning
confidence: 99%
“…(±)-2-(1-Bromopropan-2-yl)-1-((3-isopropylisoxazol-5-yl)methyl)-1H-indazol-3(2H)-one 37 (149 mg, 394 mmol) was added to a 5–10 mL microwave vial and dissolved in DMF (2.0 mL). Sodium azide (30.7 mg, 473 mmol) was added and the vial was sealed and placed in an oil bath at 60 °C for 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…We began by exploring one-pot reaction conditions that utilize in situ generated azides, prepared from the corresponding amine using the shelf-stable diazotransfer reagent 1H-imidazole-1-sulfonyl azide ( 21 ) (Scheme 3, eq 1). 17 Unfortunately, this method did not work for these oxindole substrates due to side reactions and decomposition of starting material under the diazo transfer conditions. Several solvent combinations (THF, MeOH/THF, DCM), copper reagents, and conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In previous reports, we have shown that oxazolino-2 H -indazoles, available via the Davis-Beirut reaction, 4 can be converted into N 2 -substituted indazolones by treatment with various nucleophiles 5 or N 1 , N 2 -disubstituted indazolones by treatment with various electrophiles 6 (Scheme 1). The chemistry reported here combines this electrophilic indazole → indazolone reaction with an IAAC to provide an efficient route to triazolotriazepinoindazolones {e.g., 12,13-dihydro[1,2,3]triazolo-[1′,5′:5,6][1,2,5]triazepino[1,2-a]in-dazol-10(4 H )-ones}.…”
mentioning
confidence: 99%